Orbitanın Soliter Fibröz Tümörü: Olgu Sunumu ve Literatürün Gözden Geçirilmesi - (:unkn) unknown (My University, 2015)
Soliter fibröz tümör (SFT) nadir, selim huylu, iğsi hücreli bir tümördür ve en sıklıkla visseral plevradan kaynaklanır. Plevra dışında, en sık ortaya çıktığı yerlerden biri orbitadır. Her yaşta ortaya çıkabilir, ama en sık erişkinlerde görülür ve en belirgin semptom proptozis'dir. Önemli bir cinsiyet yatkınlığı gözetmez. Orbital SFT'ler genellikle iyi prognoz gösterirler, ama yerel rekürrense meyilli habis tümörler de bildirilmiştir. Histopatolojik olarak, daha sıklıkla karşılaşılan hemanjioperisitom ile benzer özellikleri vardır. SFT tanısı immünohistokimya çalışması ile yoğun pozitif CD34 boyanmanın gösterilmesiyle konur. Burada, proptozis ve yana bakışta çift görme şikayeti ile başvuran bir orbital SFT olgusu sunuyoruz. Klinik, radyolojik, histopatolojik ve immünohistokimyasal sonuçları anlattıktan sonra mevcut literatür ışığında, kökeni ve ayırıcı tanısına yönelik bir tartışma yapacağız

Solitary fibrous tumor (SFT) is a rare, benign, spindle cell tumor that is most commonly found in the visceral pleura. The orbit is one of the most common extrapleural sites of occurrence. Though they can be seen in any age, they typically present in adults with proptosis as the prominent symptom. They show no significant gender predominance. Orbital solitary fibrous tumors routinely exhibit a benign course, but malignant forms with an increased propensity for local recurrence have been reported. Histopathologically, they share similar features with hemangiopericytoma, which is much more common. The diagnosis of SFT depends on the diffuse and intense positivity of CD34 staining by immunohistochemistry (14). Here, we report a case of SFT, which presented with proptosis and double vision on lateral gaze. We describe the clinical, radiographic, histopathological, and immunohistochemical findings. We also provide a discussion on its origin and differential diagnosis in the light of relevant literature
Solitary Fibrous Tumor of the Orbit: A Case Report And Review of the Literature
Keywords: Cerrahi